Kepemilikan Tanah Eks Eigendom Verponding 1065 Yang Ada Di Negeri Tawiri - Rizal Riski Kailul; Adonia Ivonne Laturette; Novyta Uktolseja (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2023)
Introduction: Land is a very important thing in Customary Law (can be referred to as Customary Land Law). The relationship between humans and land is closely related, namely land as a place for humans to live and continue their lives. Customary land is the property of customary law communities that have been controlled for a long time. Customary land law, known as land rights in Indonesia, such as ulayat lands, private lands, business lands, Gogolan lands, bengkok lands, agrarisch eigendom lands, and others. Purposes of the Research: This writing aims to find out the relationship between humans and the soil is very related to the land as a place for humans to live and continue their lives. While eigendom is a right of ownership to a land asset that existed during the Dutch colonial era that is subject to the provisions of Western land law in force for eigendom rights, then with the promulgation of the UUPA, the unification of Indonesian land law with the former Western rights that have not been converted to land rights as stipulated in the UUPA. Methods of the Research: legal writing that is juridical normative approach Results / Findings / Novelty of the Research: that the arrangement of compensation for the right of ownership of the Land of the former Eigendom Verponding 1065 that has not been converted is still possible to obtain proof of ownership, but not through conversion again but through granting new rights to the Office of the National Land Agency (BPN) with a certificate of ownership issued by the village head of the local area. Procedures and stages of land registration carried out by BPN Ambon on former Land objects eigendom 1065 the process of land rights derived from western rights including eigendom verponding to obtain legal certainty, by implementing the provisions of PP No.24 of 1997 consistently, well and truly will be about the right to land eigendom verponding, which ensures legal protection for holders of rights to the land of the former eigendom verponding. then the bookkeeping is simply done by giving a stamp/stamp on the evidence by writing the type of rights and rights number converted, which is regulated in PP Regulation No.24 of 1997 on land registration